Empyema necessitans and disseminated tuberculosis in an immunocompetent adult patient: A case report - Bendezú Chacaltana, Alejandra (2017)
Disseminated tuberculosis is a rare condition in immunocompetent hosts. It results from lymphohematogenous spread of Mycobacterium tuberculosis during both primary and postprimary tuberculosis. This is a case report of a male patient admitted to our hospital for typical clinical signs of infectious disease affecting lungs and joints, and a right anterior chest wall mass and right-sided pleural effusion. It was thought that he had empyema necessitans, an extension of purulent pleural fluid through adjacent tissues forming an abscess on the thoracic wall, so he was hospitalized. Nowadays, empyema necessitans is a rare clinical finding. Tuberculosis is the most common cause of empyema necessitans.